The Relationship between Maternal Knowledge and Attitudes About Dental and Oral Health with Dental Caries Status of Children at Risk of Stunting at SDN Baumata Timur - Leny Marlina A. Pinat; Christina Ngadilah; Yansestina Erlince Eky; Mery Novaria Pay; Merniawati Sherly Eluama (Dental Therapist Journal, 2023)
Dental issues in children, impacting proper tooth growth, highlight parental responsibility for a child's oral health. Children depend on their parents for dental care, and unaddressed dental caries can lead to growth disturbances and increased stunting rates. The 2021 SSGI study shows a 37.8% stunting prevalence in East Nusa Tenggara, surpassing the national rate of 24.4%, with 15 districts in NTT exceeding 30%. In 2022, the national stunting rate decreased to 21.6%, but East Nusa Tenggara maintained a dominant 35.3% rate, with Kupang City and Kupang Regency exceeding the national average at 25.1% and 24.1%, respectively. This study aims to explore the relationship between maternal knowledge and attitudes concerning oral health and the occurrence of dental caries in children at risk of stunting at SDN Baumata Timur. Utilizing a cross-sectional approach, 62 students were examined, and their Body Mass Index (BMI-for-age) identified those experiencing malnutrition. Subsequently, students with malnutrition underwent dental examinations, and their mothers completed a questionnaire. Among the 62 students, 25 were identified as malnourished. Data analysis, employing correlation and multiple regression tests with a significance level of p < 0.05, indicates that maternal knowledge is not significantly related to dental caries in children, both in permanent (DMF-T) and deciduous teeth (def-t). Conversely, maternal attitudes significantly correlate with dental caries in children in both types of teeth. Multiple regression analysis reveals no significant relationship between maternal knowledge and attitudes regarding dental health and DMF-T in elementary school children (p > 0.05). However, a more significant relationship exists between maternal attitudes toward dental health and def-t in elementary school children (p=0.010<0.05). This highlights that maternal attitudes toward children's dental health influence their behavior, particularly regarding deciduous teeth. In conclusion, while no significant relationship exists between maternal knowledge and dental caries in children, a significant association is evident between maternal attitudes and dental caries in children with malnutrition at SDN Baumata Timur.